2018
DOI: 10.1007/s10096-018-3295-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative activity of ceftobiprole against coagulase-negative staphylococci from the BSAC Bacteraemia Surveillance Programme, 2013–2015

Abstract: Coagulase-negative staphylococci (CoNS) are a significant cause of bacteraemia, the treatment of which is becoming increasingly complex due to the emergence of multidrug-resistant strains. This study aimed to evaluate the in vitro activity of ceftobiprole, an advanced-generation cephalosporin, as compared with other antimicrobial agents against CoNS from patients with bacteraemia. As part of the British Society for Antimicrobial Chemotherapy (BSAC) Bacteraemia Surveillance Programme, 650 blood isolates of CoNS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
2
7
1
Order By: Relevance
“…Multi-drug resistance has made vancomycin the first choice for anti-CoNS, and 25.5% (40/157) of patients were prescribed VAN for empirical antibiotic therapy within 72 h after the onset of CoNS bacteraemia in this study (Table 2). However, VAN-resistant CoNS does exist, for example, Anne Santerre Henriksen et al reported that 1 out of 460 isolates displayed resistance to VAN in their study [27]. For this reason, although VAN-resistant CoNS was not present in our study, we still inferred that VAN-resistant CoNS bacteraemia may appear, and it deserves our attention in the clinic.…”
Section: Discussioncontrasting
confidence: 50%
“…Multi-drug resistance has made vancomycin the first choice for anti-CoNS, and 25.5% (40/157) of patients were prescribed VAN for empirical antibiotic therapy within 72 h after the onset of CoNS bacteraemia in this study (Table 2). However, VAN-resistant CoNS does exist, for example, Anne Santerre Henriksen et al reported that 1 out of 460 isolates displayed resistance to VAN in their study [27]. For this reason, although VAN-resistant CoNS was not present in our study, we still inferred that VAN-resistant CoNS bacteraemia may appear, and it deserves our attention in the clinic.…”
Section: Discussioncontrasting
confidence: 50%
“…VAN remained the best option for the treatment of MRCoNS infections in patients with PBM. However, data from the UK and Ireland during 2013–2015 demonstrated that 0.2% of CoNS isolates were resistant to methicillin [ 26 ]. VAN-resistant CoNS exists in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Ceftobiprole, a fifth-generation broad-spectrum cephalosporin, shows activity against Gram-positive and Gram-negative bacteria and is also active against MRSA (3); in particular, it has demonstrated high affinity not only for the common PBPs but also for PBP2a (4). The antibiotic which has recently been approved has been shown to display relative stability against ␤-lactamases and a low propensity to develop resistance (3), as confirmed by the low rates of resistant staphylococcal isolates found in surveillance studies (5)(6)(7)(8). Nonetheless, some papers have described ceftobiprole resistance among MRSA strains (5,6,(9)(10)(11).…”
mentioning
confidence: 99%